1996
DOI: 10.1007/bf00142873
|View full text |Cite
|
Sign up to set email alerts
|

Soil fertility management for reclamation of Imperata grasslands by smallholder agroforestry

Abstract: Imperata cylindrica grasslands are widely believed to indicate poor soil fertility. Soil fertility improvement may have to be an important component of a reclamation strategy. Data for Sumatra, Indonesia indicate, however, that Imperata occurs on a broad range of soil types and is not confined to the poorest soils. A direct role of lmperata in soil degradation cannot be ascertained. In many instances, however, lmperata soils are low in available P and effective N supply. The use of rock phosphate in combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 7 publications
3
19
0
Order By: Relevance
“…Specifically for Sumatra, van Noordwijk et al (1997) found effects similar to those of Don et al (2011), except for lower C org losses in conversion to cropland, potentially because permanently cropped upland soils are relatively scarce in Sumatra where intensification of shifting cultivation has generally moved toward permanent tree crops (van Noordwijk et al, 2008). Imperata grasslands and areas formerly used for shifting cultivation may not have substantially lower C org than forests (Santoso et al, 1997). Soil C stock in tree plantations were reported to be 0-40% less than stocks in swidden cultivation, with the largest losses found in mechanically-established oil palm plantations (Bruun et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically for Sumatra, van Noordwijk et al (1997) found effects similar to those of Don et al (2011), except for lower C org losses in conversion to cropland, potentially because permanently cropped upland soils are relatively scarce in Sumatra where intensification of shifting cultivation has generally moved toward permanent tree crops (van Noordwijk et al, 2008). Imperata grasslands and areas formerly used for shifting cultivation may not have substantially lower C org than forests (Santoso et al, 1997). Soil C stock in tree plantations were reported to be 0-40% less than stocks in swidden cultivation, with the largest losses found in mechanically-established oil palm plantations (Bruun et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Grasses such as Cynodon dactylon, Sporobolus arabicus, Imperata cylindrica and Aeluropus lagopoides dominate the saline or saline arid habitats of the Salt Range (Chaudhry et al 2001) and are thus presumed to be well adapted to high salinity. One of these grasses, Imperata cylindrica (L.) Raeuschel, was used in the present study to determine its anatomical adaptations to salinity stress, because this grass is capable of tolerating drought and salt (Matumura and Nakajima 1988;Santoso et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…They reported the area of Imperata grasslands in Malaysia as small, at no more than 2,000 km 2 , and the largest contiguous block of this grassland was reported to be in northwest Sabah but much of this may now have been reforested with Acacia mangium for timber and pulp production. Imperata lands may have soil fertility constraints (low phosphorus and nitrogen content), but by and large are suitable in terms of topography and climate for tree crops such as the oil palm (Santoso et al 1997). Because the presence of the flammable Imperata grass can pose a fire risk as well as impede the growth of oil palms (Chikoye 2003), these lands must first be rehabilitated by weeding out the grass using herbicide or manual labour and fertilising the soil if necessary (Santoso et al 1997, p. 198).…”
Section: Concentratedmentioning
confidence: 99%